2015
DOI: 10.23917/biomedika.v7i1.1587
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Obesitas Dengan Terjadinya Osteoartritis Lutut Pada Lansia Kecamatan Laweyan Surakarta

Abstract: ABSTRAKPrevalensi osteoartritis di Indonesia mencapai 15,5% pada pria dan 12,7% pada wanita. Osteoartritis merupakan penyakit sendi degeneratif yang berkaitan dengan kerusakan kartilago sendi. Obesitas adalah kelebihan berat badan melebihi berat normal. Obesitas menjadi faktor risiko osteoartritis lutut karena terjadi penambahan berat badan yang mengakibatkan sendi lutut bekerja lebih keras. Beberapa faktor lain yang dapat menyebabkan osteoartritis antara lain bertambahnya usia, jenis kelamin, genetik, dan pek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
7
Order By: Relevance
“…23 The study results supported previous studies: there was no relationship between excess nutritional status and total cholesterol levels. 4,24 Table 2 shows no difference in respondents characteristics with changes in cholesterol levels posttest-pretest in all aspects. This indicates that cholesterol levels in the control and intervention groups are not influenced by age, sex, and nutritional status.…”
Section: Effects Of Red Dragon Fruit On Cholesterolmentioning
confidence: 92%
See 1 more Smart Citation
“…23 The study results supported previous studies: there was no relationship between excess nutritional status and total cholesterol levels. 4,24 Table 2 shows no difference in respondents characteristics with changes in cholesterol levels posttest-pretest in all aspects. This indicates that cholesterol levels in the control and intervention groups are not influenced by age, sex, and nutritional status.…”
Section: Effects Of Red Dragon Fruit On Cholesterolmentioning
confidence: 92%
“…More nutritional status is also closely related to dyslipidemia, one of which is high cholesterol levels. 3,4,5 Cholesterol is one of the most important substances in the human body. There are two types of cholesterol in the blood, namely bad cholesterol and good cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Syairul also found that there is a correlation between body mass index and knee osteoarthritis which is opposed to a study conducted by Widhianto in 2017. [13] As the results of this study is still not consistent, we aimed to find out the correlation between body mass index and the incidence of knee osteoarthritis in the Zainoel Abidin General Hospital, Banda Aceh City.…”
Section: Introductionmentioning
confidence: 92%
“…Prevalensi osteoarthritis di Indonesia mencapai 8,1% dari total penduduk. 4 Salah satu faktor risiko osteoarthritis adalah usia, prevalensi osteoarthritis meningkat seiring bertambahnya usia, dengan onset tertinggi terjadi antara usia 55 dan 64 tahun. Selama proses penuaan, masa lemak akan meningkat sehingga akan memicu peningkatan produksi adipokin dan sitokin proinflamasi.…”
Section: Aunclassified